Naqd John Hick fi Tajassud Uluhiyah Yasu' - Izzah Fitriani Muhajir (Journal of Comparative Study of Religions, 2021)
This article discusses John Hick's critique of the concept of the incarnation of God Jesus and proves the deconstruction that occurs in the concept of Christian divinity. The author uses descriptive and analytical methods to describe and analyze John Hick's thoughts. According to a study of the Bible and history conducted by John Hick, Jesus never claimed to be God or the incarnate Son of God. In Christianity, the incarnation is not the teaching of Jesus Christ but comes from Paganism which originated in Rome. The incarnation was deliberately introduced by the church to invite the enthusiasm of Christians who were not convinced by the teachings of the church at that time. Jesus who is known in the life of Christians is more appropriate to be called a prophet or a nobleman than to think of him as God. John Hick's opinion is very correct because the Bible as the basis of Christianity never says the divinity of Jesus.